A release film for ultra-light optical adhesive and its preparation process
By applying the release agent of a specific raw material combination on the base film layer and baking and curing, the problem of insufficient release force under ultraviolet rays and high temperature conditions is solved, and a stable release force and excellent release force are prepared. Release film for ultralight optical glue with glossiness.
Patent Information
- Application Number
- CN202411354273.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The release film for existing electronic optical glues has insufficient release force stability under ultraviolet irradiation and high-temperature baking conditions, and is prone to falling off due to UV light or high-temperature heat, which affects the quality of the glue.
Use polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additives, toughener and ethyl acetate to obtain a release agent through mixing and stirring, and coated on the base film. The layer was baked and cured to prepare a release film for ultralight optical glue.
The prepared ultralight optical glue release film not only has a light and stable release force, but also has excellent gloss, effectively ensuring its quality and quality.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of release film production, in particular to a release film for ultra-light optical adhesive and a preparation process thereof. Background Art
[0002] OCA optical adhesive is a transparent adhesive with variable peeling force (highly transparent acrylic double-sided adhesive without substrate). The two sides are respectively attached with an upper release film (light release force) and a lower release film (heavy release force). It is often used to bond transparent optical components such as mobile phone touch panels and lenses. It has strong filling capacity and optical uniformity. Since it has no substrate, its performance determines that it is a soft adhesive.
[0003] In the patent document with application number "CN202010341521.9" and titled "A release film for electronic optical adhesive and its preparation method", it is recorded that "its preparation raw materials include: 9-15 parts of silicone oil, 62-80 parts of solvent, 1-3 parts of catalyst, 1.5-3 parts of cross-linking agent, 2-7 parts of epoxy vinyl resin, 3-6 parts of bis{3-[3(2H benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl]-propionic acid}-polyethylene glycol 300 ester, 3-6 parts of nano zinc oxide, 2.5-5 parts of bauxite powder, and 2.5-5 parts of nano tungsten carbide-cobalt. The release film for electronic optical adhesive maintains its release force stable under ultraviolet light irradiation and high-temperature baking, and avoids it from falling off due to UV light irradiation or high-temperature heating, so as to ensure the quality of the electronic optical adhesive. The present invention also provides a method for preparing the above-mentioned release film for electronic optical adhesive."
[0004] Although the release film manufactured by the above patent document has certain mechanical advantages, its glossiness and release force performance are relatively insufficient and still need to be further improved. Based on this, the present invention provides a release film for ultra-light optical adhesive and its preparation process to solve the above technical problems. Summary of the invention
[0005] The purpose of the present invention is to provide a release film for ultra-light optical adhesive and a preparation process thereof. The prepared release film for ultra-light optical adhesive is not only light and has stable release force, but also has excellent glossiness, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a release film for ultra-light optical adhesive, the release film comprising a base film layer and a release layer arranged on one side of the base film layer, the release layer being formed by coating a release agent;
[0008] The release agent is composed of the following raw materials in parts by weight: 30-40 parts of polyethylene wax, 10-14 parts of vinyl MQ silicone resin, 8-10 parts of epoxy modified silicone resin, 2-4 parts of silicone oil, 4-7 parts of functional additives, 6-10 parts of toughening agent and 15-20 parts of ethyl acetate.
[0009] Furthermore, the preparation process of the silicone oil is as follows:
[0010] Mix appropriate amounts of tetramethylammonium hydroxide silicon alkoxide and octamethylcyclotetrasiloxane in a mass ratio of 1:0.2-0.4 at 92-94°C and 120-140 r / min for 40-50 minutes;
[0011] After the mixing is completed, 0.03% to 0.12% by mass of tetramethylammonium hydroxide siliconate (1-fluorovinyl)methyldiphenylsilane and tetramethylcyclotetrasiloxane are added thereto, and a three-stage heat preservation method is used for heat preservation treatment, and then rotary evaporation is performed for 140 to 150 minutes to obtain silicone oil.
[0012] Furthermore, the added amount of the (1-fluorovinyl)methyldiphenylsilane is 0.03% to 0.12% of the mass of tetramethylammonium hydroxide siliconate, and the added amount of the tetramethylcyclotetrasiloxane is 0.04% to 0.09% of the mass of tetramethylammonium hydroxide siliconate.
[0013] Furthermore, the three-stage insulation process is as follows:
[0014] The first stage: keep warm at 90℃ for 250-260min;
[0015] The second stage: keep warm at 125-130℃ for 30-40min;
[0016] The third stage: keep warm at 150℃ for 15 to 20 minutes.
[0017] Furthermore, the rotary evaporation has a pressure of -0.04 to -0.06 MPa and a time of 190 to 195°C.
[0018] Furthermore, the preparation process of the functional additive is as follows:
[0019] Place appropriate amounts of bauxite powder, coal gangue powder and cerium oxide in a mixing device at a mass ratio of 1:0.4-0.6:0.02-0.06, and mix at 340-440 r / min for 20-30 minutes to obtain a mixture;
[0020] The mixed material is placed in a ball mill, and ball milling balls, ethanol and water are added thereto, and the mixed material is ball milled for 60 to 70 minutes at 300 to 320 r / min, and then 0.2% to 1.2% of aluminum fluoride trihydrate by weight of the mixed material is added, and the mixed material is ball milled for 80 to 90 minutes at 420 to 440 r / min. The obtained ball milled product is vacuum dried at 80 to 90° C. to constant weight to obtain a base material;
[0021] The obtained base material is placed in a pulverizing device and pulverized to 50-100 meshes. The obtained base material powder is heated to 90-100°C and kept warm for 20-30 minutes, then heated to 1370-1400°C at a heating rate of 4-8°C / min, kept warm for 130-150 minutes, cooled to room temperature, and pulverized to 800-1000 meshes.
[0022] Furthermore, the mass ratio of the mixture, ball milling balls, ethanol and water is 1:10-12:0.5-0.8:2.2-2.8, and the diameter of the ball milling balls is 3-4 mm.
[0023] Furthermore, the toughening agent is selected from any one of nitrile rubber and styrene butadiene rubber.
[0024] The second aspect of the present invention: also provides a process for preparing the above-mentioned release film for ultra-light optical adhesive, characterized in that it comprises the following steps:
[0025] Step 1: accurately weigh polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additive, toughening agent and ethyl acetate, put silicone oil and ethyl acetate into a mixing device, and mix and stir at 120-140 r / min for 20-30 min;
[0026] Step 2: adding polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, functional additive and toughening agent, and treating at 1200-1400 r / min for 20-30 min to obtain a release agent;
[0027] Step 3: Apply the obtained release agent on the base film layer, and after baking and curing, the final product is a release film for ultra-light optical adhesive.
[0028] Furthermore, the baking and curing temperature is 70 to 100 minutes and the time is 60 to 80 minutes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] In the present invention, polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additives, toughening agent and ethyl acetate are used as raw materials, silicone oil and ethyl acetate are mixed, polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, functional additives and toughening agent are added to obtain a release agent, and finally the obtained release agent is coated on the base film layer, and after baking and curing, the final obtained is a release film for ultra-light optical adhesive. The release film for ultra-light optical adhesive prepared by the present invention is not only light, but also has a stable release force, and also has excellent gloss, which effectively guarantees its quality. The release film for ultra-light optical adhesive and the preparation process thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1: This embodiment provides a release film for ultra-light optical adhesive, the release film comprising a base film layer and a release layer disposed on one side of the base film layer, the release layer being formed by coating a release agent;
[0033] The release agent is composed of the following raw materials in parts by weight: 30 parts of polyethylene wax, 10 parts of vinyl MQ silicone resin, 8 parts of epoxy modified silicone resin, 2 parts of silicone oil, 4 parts of functional additives, 6 parts of toughening agent and 15 parts of ethyl acetate.
[0034] In this embodiment, it should be noted that the base film layer is made of PET film, the polyethylene wax is purchased from Jinan Shanhai Chemical Technology Co., Ltd., the vinyl MQ silicone resin is purchased from Hubei Longsheng Sihai New Materials Co., Ltd., and the epoxy-modified silicone resin is purchased from Hubei Longsheng Sihai New Materials Co., Ltd.
[0035] Among them, the preparation process of silicone oil is as follows:
[0036] Mix appropriate amounts of tetramethylammonium hydroxide silicon alkoxide and octamethylcyclotetrasiloxane in a mass ratio of 1:0.2 at 92°C and 120 r / min for 40 min;
[0037] After the mixing is completed, (1-fluorovinyl)methyldiphenylsilane and tetramethylcyclotetrasiloxane with a content of 0.03% by weight of tetramethylammonium hydroxide siliconate are added thereto, and the mixture is heat-insulated in a three-stage heat-insulating manner, and then rotary evaporated for 140 to 150 minutes to obtain silicone oil.
[0038] Further, the added amount of (1-fluorovinyl)methyldiphenylsilane is 0.03% of the mass of tetramethylammonium hydroxide silicon alkoxide, and the added amount of tetramethylcyclotetrasiloxane is 0.04% of the mass of tetramethylammonium hydroxide silicon alkoxide.
[0039] In addition, the three-stage insulation process is as follows:
[0040] Stage 1: Keep warm at 90°C for 250 minutes;
[0041] The second stage: keep warm at 125℃ for 30min;
[0042] The third stage: keep warm at 150℃ for 15 minutes.
[0043] Furthermore, the pressure of the rotary evaporation was -0.04 MPa and the time was 190°C.
[0044] The preparation process of the functional additive is as follows:
[0045] Place appropriate amounts of bauxite powder, coal gangue powder and cerium oxide in a mixing device at a mass ratio of 1:0.4:0.02, and mix at 340 r / min for 20 minutes to obtain a mixture;
[0046] The mixture is placed in a ball mill, and ball milling balls, ethanol and water are added thereto, and the mixture is ball milled at 300 r / min for 60 min, and then 0.2% of the weight of the mixture is aluminum fluoride trihydrate, and the mixture is ball milled at 420 r / min for 80 min. The obtained ball milled product is vacuum dried at 80° C. to constant weight to obtain a base material;
[0047] The obtained base material is placed in a pulverizing device and pulverized to 50 mesh. The obtained base material powder is heated to 90°C and kept warm for 20 minutes, then heated to 1370°C at a heating rate of 4°C / min, kept warm for 130 minutes, cooled to room temperature, and pulverized to 800 mesh.
[0048] In this embodiment, it should be noted that bauxite powder was purchased from Shijiazhuang Chengao New Material Technology Co., Ltd., and coal gangue powder was purchased from Hebei Jiegui Mineral Products Co., Ltd.
[0049] Furthermore, the added mass ratio of the mixture, ball milling balls, ethanol and water is 1:10:0.5:2.2, and the diameter of the ball milling balls is 3 mm.
[0050] Among them, the toughening agent is nitrile rubber.
[0051] In this embodiment, it should be noted that the nitrile rubber was purchased from Sichuan Xintianhai Chemical Co., Ltd.
[0052] In addition, this embodiment also provides a preparation process of the above-mentioned release film for ultra-light optical adhesive, which is characterized by comprising the following steps:
[0053] Step 1: accurately weigh polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additive, toughening agent and ethyl acetate, put silicone oil and ethyl acetate into a mixing device, and mix and stir at 120 r / min for 20 minutes;
[0054] Step 2: adding polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, functional additives and toughening agent, and treating at 1200 r / min for 20 min to obtain a release agent;
[0055] Step 3: Apply the obtained release agent on the base film layer, and after baking and curing, the final product is a release film for ultra-light optical adhesive.
[0056] Furthermore, the baking and curing temperature is 70 minutes and the time is 60 minutes.
[0057] Example 2: The preparation process of the release film for ultra-light optical adhesive provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation process of the release film for ultra-light optical adhesive in this example are different; the specific raw material composition and the specific preparation process of the release film for ultra-light optical adhesive in this example are as follows:
[0058] A release film for ultra-light optical adhesive, the release film comprising a base film layer and a release layer arranged on one side of the base film layer, the release layer being formed by coating a release agent;
[0059] The release agent is composed of the following raw materials in parts by weight: 35 parts of polyethylene wax, 12 parts of vinyl MQ silicone resin, 9 parts of epoxy modified silicone resin, 3 parts of silicone oil, 5 parts of functional additives, 8 parts of toughening agent and 17 parts of ethyl acetate.
[0060] In this embodiment, it should be noted that the base film layer is made of PET film, the polyethylene wax is purchased from Jinan Shanhai Chemical Technology Co., Ltd., the vinyl MQ silicone resin is purchased from Hubei Longsheng Sihai New Materials Co., Ltd., and the epoxy-modified silicone resin is purchased from Hubei Longsheng Sihai New Materials Co., Ltd.
[0061] Among them, the preparation process of silicone oil is as follows:
[0062] Mix appropriate amounts of tetramethylammonium hydroxide silicon alkoxide and octamethylcyclotetrasiloxane in a mass ratio of 1:0.3 at 93°C and 130 r / min for 45 min;
[0063] After the mixing is completed, (1-fluorovinyl)methyldiphenylsilane and tetramethylcyclotetrasiloxane with a mass percentage of 0.07% of tetramethylammonium hydroxide siliconate are added thereto, and the mixture is heat-insulated in a three-stage heat-insulating manner, and then rotary evaporated for 145 minutes to obtain silicone oil.
[0064] Further, the added amount of (1-fluorovinyl)methyldiphenylsilane is 0.08% of the mass of tetramethylammonium hydroxide silicon alkoxide, and the added amount of tetramethylcyclotetrasiloxane is 0.06% of the mass of tetramethylammonium hydroxide silicon alkoxide.
[0065] In addition, the three-stage insulation process is as follows:
[0066] Stage 1: Keep warm at 90°C for 255 minutes;
[0067] The second stage: keep warm at 127℃ for 35min;
[0068] The third stage: keep warm at 150℃ for 17 minutes.
[0069] Furthermore, the pressure of the rotary evaporation was -0.05 MPa and the time was 192°C.
[0070] The preparation process of the functional additive is as follows:
[0071] Place appropriate amounts of bauxite powder, coal gangue powder and cerium oxide in a mixing device at a mass ratio of 1:0.5:0.04, and mix at 390 r / min for 25 min to obtain a mixture;
[0072] The mixture is placed in a ball mill, and ball milling balls, ethanol and water are added thereto, and the mixture is ball milled at 310 r / min for 65 min, and then 0.7% of aluminum fluoride trihydrate by weight of the mixture is added, and the mixture is ball milled at 430 r / min for 80 to 90 min. The obtained ball milled product is vacuum dried at 80 to 90° C. to constant weight to obtain a base material;
[0073] The obtained base material is placed in a pulverizing device and pulverized to 75 mesh. The obtained base material powder is heated to 95°C and kept warm for 25 minutes, then heated to 1385°C at a heating rate of 6°C / min and kept warm for 140 minutes, cooled to room temperature, and pulverized to 900 mesh.
[0074] In this embodiment, it should be noted that bauxite powder was purchased from Shijiazhuang Chengao New Material Technology Co., Ltd., and coal gangue powder was purchased from Hebei Jiegui Mineral Products Co., Ltd.
[0075] Furthermore, the added mass ratio of the mixture, ball milling balls, ethanol and water is 1:11:0.6:2.6, and the diameter of the ball milling balls is 4 mm.
[0076] Among them, the toughening agent is nitrile rubber.
[0077] In this embodiment, it should be noted that the nitrile rubber was purchased from Sichuan Xintianhai Chemical Co., Ltd.
[0078] In addition, this embodiment also provides a preparation process of the above-mentioned release film for ultra-light optical adhesive, which is characterized by comprising the following steps:
[0079] Step 1: accurately weigh polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additive, toughening agent and ethyl acetate, put silicone oil and ethyl acetate into a mixing device, and mix and stir at 130 r / min for 25 minutes;
[0080] Step 2: adding polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, functional additive and toughening agent, and treating at 1300 r / min for 25 min to obtain a release agent;
[0081] Step 3: Apply the obtained release agent on the base film layer, and after baking and curing, the final product is a release film for ultra-light optical adhesive.
[0082] Furthermore, the baking and curing temperature is 85 minutes and the time is 70 minutes.
[0083] Example 3: The preparation process of the release film for ultra-light optical adhesive provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation process of the release film for ultra-light optical adhesive in this example are different; the specific raw material composition and the specific preparation process of the release film for ultra-light optical adhesive in this example are as follows:
[0084] A release film for ultra-light optical adhesive, the release film comprising a base film layer and a release layer arranged on one side of the base film layer, the release layer being formed by coating a release agent;
[0085] The release agent is composed of the following raw materials in parts by weight: 40 parts of polyethylene wax, 14 parts of vinyl MQ silicone resin, 10 parts of epoxy modified silicone resin, 4 parts of silicone oil, 7 parts of functional additives, 10 parts of toughening agent and 20 parts of ethyl acetate.
[0086] In this embodiment, it should be noted that the base film layer is made of PET film, the polyethylene wax is purchased from Jinan Shanhai Chemical Technology Co., Ltd., the vinyl MQ silicone resin is purchased from Hubei Longsheng Sihai New Materials Co., Ltd., and the epoxy-modified silicone resin is purchased from Hubei Longsheng Sihai New Materials Co., Ltd.
[0087] Among them, the preparation process of silicone oil is as follows:
[0088] Mix appropriate amounts of tetramethylammonium hydroxide silicon alkoxide and octamethylcyclotetrasiloxane in a mass ratio of 1:0.4 at 94°C and 140 r / min for 50 min;
[0089] After the mixing is completed, (1-fluorovinyl)methyldiphenylsilane and tetramethylcyclotetrasiloxane with a mass percentage of 0.12% of tetramethylammonium hydroxide siliconate are added thereto, and the mixture is heat-insulated in a three-stage heat-insulating manner, and then rotary evaporated for 150 minutes to obtain silicone oil.
[0090] Further, the added amount of (1-fluorovinyl)methyldiphenylsilane is 0.12% of the mass of tetramethylammonium hydroxide silicon alkoxide, and the added amount of tetramethylcyclotetrasiloxane is 0.09% of the mass of tetramethylammonium hydroxide silicon alkoxide.
[0091] In addition, the three-stage insulation process is as follows:
[0092] Stage 1: Keep warm at 90°C for 260 minutes;
[0093] The second stage: keep warm at 130℃ for 40min;
[0094] The third stage: keep warm at 150℃ for 20 minutes.
[0095] Furthermore, the pressure of the rotary evaporation was -0.06 MPa and the time was 195°C.
[0096] The preparation process of the functional additive is as follows:
[0097] Place appropriate amounts of bauxite powder, coal gangue powder and cerium oxide in a mixing device at a mass ratio of 1:0.6:0.06, and mix at 440 r / min for 30 minutes to obtain a mixture;
[0098] The mixture is placed in a ball mill, and ball milling balls, ethanol and water are added thereto, and the mixture is ball milled at 320 r / min for 70 min, and then 1.2% of aluminum fluoride trihydrate by weight of the mixture is added, and the mixture is ball milled at 440 r / min for 90 min. The obtained ball milled product is vacuum dried at 90° C. to constant weight to obtain a base material;
[0099] The obtained base material is placed in a pulverizing device and pulverized to 100 mesh. The obtained base material powder is heated to 100°C and kept warm for 30 minutes, then heated to 1400°C at a heating rate of 8°C / min, kept warm for 150 minutes, cooled to room temperature, and pulverized to 1000 mesh.
[0100] In this embodiment, it should be noted that bauxite powder was purchased from Shijiazhuang Chengao New Material Technology Co., Ltd., and coal gangue powder was purchased from Hebei Jiegui Mineral Products Co., Ltd.
[0101] Furthermore, the added mass ratio of the mixture, ball milling balls, ethanol and water is 1:12:0.8:2.8, and the diameter of the ball milling balls is 4 mm.
[0102] Among them, the toughening agent is styrene-butadiene rubber.
[0103] In this embodiment, it should be noted that the styrene-butadiene rubber was purchased from Laizhou Yasheng Rubber & Plastic Co., Ltd.
[0104] In addition, this embodiment also provides a preparation process of the above-mentioned release film for ultra-light optical adhesive, which is characterized by comprising the following steps:
[0105] Step 1, accurately weigh polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additives, toughening agent and ethyl acetate, put silicone oil and ethyl acetate into a mixing device, and mix and stir at 140r / min for 30min;
[0106] Step 2: adding polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, functional additive and toughening agent, and treating at 1400 r / min for 30 min to obtain a release agent;
[0107] Step 3: Apply the obtained release agent on the base film layer, and after baking and curing, the final product is a release film for ultra-light optical adhesive.
[0108] Furthermore, the curing temperature is 100 min and the curing time is 80 min.
[0109] Comparative Example 1: The difference from Example 1 is that in this example, an equal amount of fluorinated polysiloxane (purchased from Wuhan Jushun Chemical Co., Ltd.) is used instead of silicone oil.
[0110] Comparative Example 2: The difference from Example 1 is that the preparation process of the silicone oil in this example does not contain the second stage.
[0111] Comparative Example 3: The difference from Example 1 is that an equal amount of bauxite powder is used to replace the functional additive in this example.
[0112] Performance test: The ultra-light optical adhesive release film samples provided in Examples 1 to 3 and Comparative Examples 1 to 3 are marked as Examples 1 to 3 and Comparative Examples 1 to 3, respectively; and the relevant properties of the ultra-light optical adhesive release film provided in Examples 1 to 3 and Comparative Examples 1 to 3 are tested as follows:
[0113] 1. Release force test: The test method is TESA7475 standard tape, peeling at 300mm / min and 180℃.
[0114] 2. Gloss test: The test method is to use a gloss meter at a 60° angle to test each set of release films to obtain their corresponding gloss.
[0115] The obtained test data are recorded in Table 1 and Table 2 below.
[0116]
[0117]
[0118] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the ultra-light optical adhesive release film prepared by the present invention is not only light, but also has a stable release force, and also has excellent glossiness, which effectively guarantees its quality. This shows that the ultra-light optical adhesive release film and the preparation process thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0119] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0120] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A release film for ultra-light optical adhesive, characterized in that: The release film comprises a base film layer and a release layer arranged on one side of the base film layer, and the release layer is formed by coating a release agent; The release agent is composed of the following raw materials in parts by weight: 30 to 40 parts of polyethylene wax, 10 to 14 parts of vinyl MQ silicone resin, 8 to 10 parts of epoxy modified silicone resin, 2 to 4 parts of silicone oil, 4 to 7 parts of functional additives, 6 to 10 parts of toughening agent and 15 to 20 parts of ethyl acetate; The preparation process of the silicone oil is as follows: Mix appropriate amounts of tetramethylammonium hydroxide silicon alkoxide and octamethylcyclotetrasiloxane in a mass ratio of 1:0.2-0.4 at 92-94°C and 120-140 r / min for 40-50 minutes; After the mixing is completed, 0.03% to 0.12% by mass of tetramethylammonium hydroxide silicon alkoxide (1-fluorovinyl)methyldiphenylsilane and tetramethylcyclotetrasiloxane are added thereto, and a three-stage heat preservation method is used for heat preservation treatment, and then rotary evaporation is performed for 140 to 150 minutes to obtain silicone oil; The preparation process of the functional additive is as follows: Place appropriate amounts of bauxite powder, coal gangue powder and cerium oxide in a mixing device at a mass ratio of 1:0.4-0.6:0.02-0.06, and mix at 340-440 r / min for 20-30 minutes to obtain a mixture; The mixed material is placed in a ball mill, and ball milling balls, ethanol and water are added thereto, and the mixed material is ball milled for 60 to 70 minutes at 300 to 320 r / min, and then 0.2% to 1.2% of aluminum fluoride trihydrate by weight of the mixed material is added, and the mixed material is ball milled for 80 to 90 minutes at 420 to 440 r / min. The obtained ball milled product is vacuum dried at 80 to 90° C. to constant weight to obtain a base material; The obtained base material is placed in a pulverizing device and pulverized to 50-100 meshes. The obtained base material powder is heated to 90-100°C and kept warm for 20-30 minutes, then heated to 1370-1400°C at a heating rate of 4-8°C / min, kept warm for 130-150 minutes, cooled to room temperature, and pulverized to 800-1000 meshes.
2. The release film for ultra-light optical adhesive according to claim 1, characterized in that: The added amount of the (1-fluorovinyl)methyldiphenylsilane is 0.03% to 0.12% of the mass of tetramethylammonium hydroxide silicon alkoxide, and the added amount of the tetramethylcyclotetrasiloxane is 0.04% to 0.09% of the mass of tetramethylammonium hydroxide silicon alkoxide.
3. The release film for ultra-light optical adhesive according to claim 1, characterized in that: The three-stage insulation process is as follows: The first stage: keep warm at 90℃ for 250-260min; The second stage: keep warm at 125-130℃ for 30-40min; The third stage: keep warm at 150℃ for 15 to 20 minutes.
4. The release film for ultra-light optical adhesive according to claim 1, characterized in that: The rotary evaporation pressure is -0.04 to -0.06 MPa, and the time is 190 to 195°C.
5. The release film for ultra-light optical adhesive according to claim 1, characterized in that: The added mass ratio of the mixed material, ball milling balls, ethanol and water is 1:10-12:0.5-0.8:2.2-2.8, and the diameter of the ball milling balls is 3-4 mm.
6. The release film for ultra-light optical adhesive according to claim 1, characterized in that: The toughening agent is selected from any one of nitrile rubber and styrene butadiene rubber.
7. A process for preparing a release film for ultra-light optical adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: accurately weigh polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, silicone oil, functional additive, toughening agent and ethyl acetate, put silicone oil and ethyl acetate into a mixing device, and mix and stir at 120-140 r / min for 20-30 min; Step 2: adding polyethylene wax, vinyl MQ silicone resin, epoxy modified silicone resin, functional additive and toughening agent, and treating at 1200-1400 r / min for 20-30 min to obtain a release agent; Step 3: Apply the obtained release agent on the base film layer, and after baking and curing, the final product is a release film for ultra-light optical adhesive.
8. The process for preparing a release film for ultra-light optical adhesive according to claim 7, characterized in that: The baking and curing process is performed at a temperature of 70 to 100 minutes and for a time of 60 to 80 minutes.
Citation Information
Patent Citations
A release film for electronic optical adhesives and its preparation method
CN111334219B
Release film with ultralight release force and preparation method thereof
CN106221595A
Stain-resistant release film with small release force
CN106243372A